1999
DOI: 10.1093/glycob/9.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Nonglucosylated oligosaccharides are transferred to protein in MI8-5 Chinese hamster ovary cells

Abstract: A CHO mutant MI8-5 was found to synthesize Man9-GlcNAc2-P-P-dolichol rather than Glc3Man9GlcNAc2-P-P-dolichol as the oligosaccharide-lipid intermediate in N-glycosylation of proteins. MI8-5 cells were incubated with labeled mevalonate, and the prenol was found to be dolichol. The mannose-labeled oligosaccharide released from oligosaccharide-lipid of MI8-5 cells was analyzed by HPLC and alpha-mannosidase treatment, and the data were consistent with a structure of Man9GlcNAc2. In addition, MI8-5 cells did not in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 32 publications
3
28
0
Order By: Relevance
“…The quenching method that was modified from previous reports provides reliable results of the instantaneous steady state levels of LLO in cell lines (Jones et al, 2010) or tissues (Gao and Lehrman, 2006) It is well known that glucose starvation alters the LLO composition. In 25 mM glucose culture, LLO composition is consistent with previous studies (Jones et al, 2010;Quellhorst et al, 1999;Rearick et al, 1981), showing M9-P-P-Dol as the primary LLO found in CHO-K1 cells, along with small amounts of Glc2Man9GlcNAc2, Glc1Man9GlcNAc2, and Man9GlcNAc2 due to the possible reason that an addition of glucose residues onto the fully mannosylated LLO (Man9GlcNAc2-P-P-Dol) is the rate determined step (Jones et al, 2010). Glucose starvation can induce an accumulation of truncated LLO intermediates in the early stage of N-glycosylation, such as M5 to M2 (Rearick et al, 1981), which is consistent with LLO pools extracted from cells grown in 0-15 mM glucose.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The quenching method that was modified from previous reports provides reliable results of the instantaneous steady state levels of LLO in cell lines (Jones et al, 2010) or tissues (Gao and Lehrman, 2006) It is well known that glucose starvation alters the LLO composition. In 25 mM glucose culture, LLO composition is consistent with previous studies (Jones et al, 2010;Quellhorst et al, 1999;Rearick et al, 1981), showing M9-P-P-Dol as the primary LLO found in CHO-K1 cells, along with small amounts of Glc2Man9GlcNAc2, Glc1Man9GlcNAc2, and Man9GlcNAc2 due to the possible reason that an addition of glucose residues onto the fully mannosylated LLO (Man9GlcNAc2-P-P-Dol) is the rate determined step (Jones et al, 2010). Glucose starvation can induce an accumulation of truncated LLO intermediates in the early stage of N-glycosylation, such as M5 to M2 (Rearick et al, 1981), which is consistent with LLO pools extracted from cells grown in 0-15 mM glucose.…”
Section: Discussionsupporting
confidence: 91%
“…Cells were seeded in high density in media containing glucose from 0-25 mM, and incubated for 24 h. In chapter 3 we found that cells in culture with an initial glucose concentration 15 mM had been in a glucose depleted state for nearly 4 h. Cells in lower glucose concentration (<15 mM) were No evidence has been found between extracellular galactosidase and galactose content (Gramer et al, 2011;Jones et al, 2010;Quellhorst et al, 1999;Rearick et al, 1981). The results showed a linear correlation between the time period of glucose depletion during 24 h and galactosylation and sialylation indexes, suggesting that the decrease in galactosylation and sialylation could be elicited by depletion of activated monosacharides as dolichol phosphate or nucleotide derivates, mostly glucose-derived substrates.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Instead, it comigrated with an R f similar to that of Man 9 GlcNAc 2 (Fig. 5A, lane 2), the species found in MI8-5, a CHO mutant defective in glucosylation of the N-glycan precursor (28) and with an authentic nonradioactive Man 9 GlcNAc 2 standard. The lack of OSL glucosylation is consistent with OSL structures in other trypanosomatids (24).…”
Section: Vol 3 2004 Characterization Of a T Brucei Glycosylation Mmentioning
confidence: 95%